Hypoxemia, hypoglycemia and IMCI danger signs in pediatric outpatients in Malawi. - André Thunberg; Beatiwel Zadutsa; Everlisto Phiri; Carina King; Josephine Langton; Lumbani Banda; Charles Makwenda; Helena Hildenwall (Public Library of Science (PLoS), 2022)
Hypoxemia and hypoglycemia are known risks for mortality in children in low-income settings. Routine screening with pulse oximetry and blood glucose assessments for outpatients could assist in early identification of high-risk children. We assessed the prevalence of hypoglycemia and hypoxemia, and the overlap with Integrated Management of Childhood Illness (IMCI) general danger signs, among children seeking outpatient care in Malawi. A cross-sectional study was conducted at 14 government primary care facilities, four rural hospitals and one district referral hospital in Mchinji district, Malawi from August 2019-April 2020. All children aged 0-12 years seeking care with an acute illness were assessed on one day per month in each facility. Study research assistants measured oxygen saturation using Lifebox LB-01 pulse oximeter and blood glucose was assessed with AccuCheck Aviva glucometers. World Health Organization definitions were used for severe hypoglycemia (<2.5mmol/l) and hypoxemia (SpO2 <90%). Moderate hypoglycemia (2.5-4.0mmol/l) and hypoxemia (SpO2 90-93%) were also calculated and prevalence levels compared between those with and without IMCI danger signs using chi2 tests. In total 2,943 children were enrolled, with a median age of 41 (range: 0-144) months. The prevalence of severe hypoxemia was 0.6% and moderate hypoxemia 5.4%. Severe hypoglycemia was present in 0.1% of children and moderate hypoglycemia in 11.1%. IMCI general danger signs were present in 29.3% of children. All severely hypoglycemic children presented with an IMCI danger sign (p <0.001), but only 23.5% of the severely hypoxemic and 31.7% of the moderately hypoxemic children. We conclude that while the prevalence of severe hypoxemia and hypoglycemia were low, moderate levels were not uncommon and could potentially be useful as an objective tool to determine referral needs. IMCI danger signs identified hypoglycemic children, but results highlight the challenge to detect hypoxemia. Future studies should explore case management strategies for moderate hypoxemia and hypoglycemia.